1990
DOI: 10.3109/00016489009122520
|View full text |Cite
|
Sign up to set email alerts
|

Human Middle Ear Gas Composition Studied by Mass Spectrometry

Abstract: The purpose of this study was to develop a procedure for mass spectrometric measurement fitted to analyse the human middle ear gas composition, and to determine the partial pressures of the middle ear gases in adults with healthy ears. To avoid the risks of admixture of the gas sample with atmospheric air we used "on-line" sampling from the middle ear to the analysing equipment, and a new protective technique at the site of puncture. The inlet system was modified to achieve sufficiently low gas consumption. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 15 publications
3
58
0
Order By: Relevance
“…The obstruction shut off the pathway of oxygen exchanges between the air and the cavity. The oxygen tension varies from 44 to 54 mm Hg in healthy ears [39,40] , but may be lower in the course of SOM. The influence of oxygen tension on the middle ear ion transport functions has revealed that prolonged incubation of the middle ear epithelial cells in moderate hypoxia (32 mm Hg) resulted in a reversible decrease in sodium transport.…”
Section: Discussionmentioning
confidence: 99%
“…The obstruction shut off the pathway of oxygen exchanges between the air and the cavity. The oxygen tension varies from 44 to 54 mm Hg in healthy ears [39,40] , but may be lower in the course of SOM. The influence of oxygen tension on the middle ear ion transport functions has revealed that prolonged incubation of the middle ear epithelial cells in moderate hypoxia (32 mm Hg) resulted in a reversible decrease in sodium transport.…”
Section: Discussionmentioning
confidence: 99%
“…The rest is a mixture of biologically active gases, carbon dioxide (seven per cent), water vapour (six per cent), and oxygen (5.5 per cent). 5 The area of the cell system is greatly enhanced by bony septa by which the volume is subdivided into a large number of small cavities. The bony septa are lined by a thin one-layered cubical respiratory epithelium that for the most part lacks cilia and goblet cells.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of exchange of these gases between the ME and blood determines the net volume of transmucosal gas exchange. For N 2 , a difference in ME to blood partial pressure of up to ϳ50 Torr has been reported, whereas that of O 2 and CO 2 is nearly zero (16,26,33). Therefore, the net volume gas loss that we have observed in the steady state (30) should result mainly from transmucosal N 2 exchange.…”
mentioning
confidence: 80%